PENGENALAN BAHASA INGGRIS UNTUK TINGKAT PEMULA DI SEKOLAH DASAR YPK ONGGAYA DISTRIK NAUKENJERAI - Marnina Marnina; Marni Bawawa (Musamus University, 2020)
The implementation of community service activities is aimed at students of the YPK Onggaya Elementary School in the Naukenjerai District of Merauke so that students can understand and know English as a foreign language as an effort to increase students' interest, motivation, willingness and interest in learning English in the field of education. Increasing competence in learning English is one of the useful activities in order to improve the quality and quality of a student. The introduction of English by Young Learners as a foreign language as an effort to increase the willingness and interest of students at the YPK Onggaya District Naukenjerai District also aims to provide knowledge for students about learning English and its benefits